Optimization of the Self-Healing Efficiency of Bacterial Concrete Using Impregnation of Three Different Precursors into Lightweight Aggregate. Issue 3 (March 2023) - Omar, Omar; Mousa, Momen R.; Hassan, Marwa; Hungria, Ricardo; Gavilanes, Andrea; Arce, Gabriel; Milla, Jose; Rupnow, Tyson
Implementation of self-healing concrete technologies is a promising approach to enhance the durability of the transportation infrastructure. Among these technologies, bacterial concrete has the potential to seal microcracks through microbial-induced calcite precipitation (MICP). To ensure the viability of this technology, bacterial protection is essential given concrete's harsh environment. Additionally, the success of this technology depends on the presence of an adequate mineral precursor compound and nutrient for the bacteria. As such, the main objective of this study was to optimize the healing efficiency of bacterial concrete in subtropical climates through the vacuum impregnation of bacteria into a lightweight aggregate (LWA). To achieve this objective, mortar samples were prepared while incorporating different combinations of precursors (magnesium acetate, calcium lactate, and sodium lactate) and alkali-resistant healing agent Bacillus pseudofirmus bacteria (with and without). In addition, a control sample was prepared without bacteria or precursors for comparative purposes. For each sample, three mortar cubes and three mortar beams were cast and used to evaluate the compressive strength, crack healing efficiency, and flexural strength recovery. Additionally, the morphology of healing products was observed in bacteria-containing samples under scanning electron microscopy with energy x-ray dispersive spectroscopy using a scanning electron microscope (SEM) with EDAX Pegasus energy dispersive spectroscopy (EDS). Results showed that self-healing bacterial concrete could be optimized (without significant reduction in mechanical properties) if Bacillus pseudofirmus bacteria at a concentration of 10 8 cells/ml and sodium lactate precursor at a concentration of 75 mM/l were impregnated into lightweight aggregate.